2013
DOI: 10.1186/1749-8090-8-110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the intraoperative specimens of the thoracic and abdominal aorta

Abstract: BackgroundLittle is known about the histological patterns of acute and chronic aortic pathology with regard to medial degeneration, atherosclerosis and aortitis as well as their distribution in different age groups. The aim of the study was to evaluate histopathological findings of intraoperatively gained aortic specimens with regard to the incidence of medial degeneration, atherosclerosis and aortitis.MethodsIntraoperatively gained aortic specimens were evaluated in 151 patients including 83 (55%) aortic aneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Hypertension is a known risk factor for acute type A aortic dissection, and other factors, such as atherosclerosis, also likely contribute to the weakening of the aortic wall. 15,16 In our study, hypertension was a comorbidity present in all participants, and we are unable to determine the exact role that the presence of this or other comorbidities played in the need for aortic reoperation. While patients with history of vasculitis, chronic inflammatory disease, or autoimmune disease were excluded from enrollment, such history relied on the patient's own report, and the possibility of undiagnosed disorders should be considered.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Hypertension is a known risk factor for acute type A aortic dissection, and other factors, such as atherosclerosis, also likely contribute to the weakening of the aortic wall. 15,16 In our study, hypertension was a comorbidity present in all participants, and we are unable to determine the exact role that the presence of this or other comorbidities played in the need for aortic reoperation. While patients with history of vasculitis, chronic inflammatory disease, or autoimmune disease were excluded from enrollment, such history relied on the patient's own report, and the possibility of undiagnosed disorders should be considered.…”
Section: Discussionmentioning
confidence: 74%
“…Possible causes include cystic medial degeneration, atherosclerosis, or medial ischemia due to disruption of the vasa vasorum. [15][16][17] Mismatch between the mechanical properties of the adhesive and graft material used has also been proposed as a mechanism of pseudoaneurysm formation, particularly in cases without an associated inflammatory reaction. 1 Aortic tissue from 1 patient exhibited a marked inflammatory response consisting of a necrotizing granulomatous inflammatory infiltrate, which was not observed in tissue samples from any other patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For years, degenerative atherosclerotic changes in aortic wall have been blamed for the development of aneurysm of descending aorta. At the same time, some authors [4]- [7] underline a number of significant differences between atherosclerosis and aneurysm. Thus, atherosclerosis is primarily localized in the intima and is productive due to accumulated atherosclerotic plaques, which contributes to the development of aortoiliac occlusive disease (Leriche's syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pathologic studies suggest that on average at all ages the amount of calcium is higher in the tunica media compared to the intima [13], [14]. Additionally, Juraszek et al [15] observed a clear association between medial degeneration and type A aortic dissections in patients below 65 years of age, while in those above 65 years type A aortic dissections were associated with atherosclerosis. Thin, mainly circular, wall calcifications in the tunica media are associated with aortic stiffening, increased pulse pressure, reduced coronary blood flow and left ventricular hypertrophy [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%